2020
DOI: 10.1038/s41467-020-14951-4
|View full text |Cite
|
Sign up to set email alerts
|

A comparative genomics methodology reveals a widespread family of membrane-disrupting T6SS effectors

Abstract: Gram-negative bacteria deliver effectors via the type VI secretion system (T6SS) to outcompete their rivals. Each bacterial strain carries a different arsenal of effectors; the identities of many remain unknown. Here, we present an approach to identify T6SS effectors encoded in bacterial genomes of interest, without prior knowledge of the effectors' domain content or genetic neighborhood. Our pipeline comprises a comparative genomics analysis followed by screening using a surrogate T6SS + strain. Using this ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
120
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(127 citation statements)
references
References 72 publications
0
120
0
Order By: Relevance
“…T6SS membrane disrupting effectors (Tme) or pore‐forming toxins exert their toxicity from the periplasm of the target cells, by inserting into the inner membrane and causing membrane depolarization. Unlike other effectors, Tme effectors do not possess catalytic activity and induce growth inhibition rather than cell lysis (Fridman et al, 2020; LaCourse et al, 2018; Mariano et al, 2019; Miyata et al, 2013). These effectors share homologies with pore‐forming colicins or have predicted transmembrane helices (TMH) in their C‐terminal region (Fridman et al, 2020; LaCourse et al, 2018; Miyata et al, 2011).…”
Section: Activity Of T6ss Delivered Effectorsmentioning
confidence: 99%
See 3 more Smart Citations
“…T6SS membrane disrupting effectors (Tme) or pore‐forming toxins exert their toxicity from the periplasm of the target cells, by inserting into the inner membrane and causing membrane depolarization. Unlike other effectors, Tme effectors do not possess catalytic activity and induce growth inhibition rather than cell lysis (Fridman et al, 2020; LaCourse et al, 2018; Mariano et al, 2019; Miyata et al, 2013). These effectors share homologies with pore‐forming colicins or have predicted transmembrane helices (TMH) in their C‐terminal region (Fridman et al, 2020; LaCourse et al, 2018; Miyata et al, 2011).…”
Section: Activity Of T6ss Delivered Effectorsmentioning
confidence: 99%
“…Unlike other effectors, Tme effectors do not possess catalytic activity and induce growth inhibition rather than cell lysis (Fridman et al, 2020; LaCourse et al, 2018; Mariano et al, 2019; Miyata et al, 2013). These effectors share homologies with pore‐forming colicins or have predicted transmembrane helices (TMH) in their C‐terminal region (Fridman et al, 2020; LaCourse et al, 2018; Miyata et al, 2011). These TMH can bear glycine zipper motifs (LaCourse et al, 2018), a motif commonly found in channel proteins or amyloid proteins and known to promote homo‐dimerization (Kim et al, 2005; LaCourse et al, 2018).…”
Section: Activity Of T6ss Delivered Effectorsmentioning
confidence: 99%
See 2 more Smart Citations
“…One possible intervention, as suggested by Unterweger et al [128], would allow non-pathogenic commensal bacteria such as these N. subflava biovar perflava possessing the T6SS to outcompete pathogens such as N. meningitidis and N. gonorrhoeae within a specific niche. The T6SS effector proteins, which are antibacterial to competitor species, have also been proposed to be developed as therapeutic agents against multidrug-resistant bacterial pathogens [129].…”
Section: First Identification Of a Type VI Secretion System In The Nementioning
confidence: 99%